Implementing the SLA negotiation in manufacturing grid. Issue 4 (9th February 2009) - Liu, Lilan; Sun, Haiyang; Yu, Tao; Cai, Hongxia
Service level agreement (SLA) negotiation plays a very important role in manufacturing grid. In order to solve its problem of practical application, firstly, we try the Nash negotiation method. Because the method depends on the negotiators' utility functions and it is impracticable to construct the different players' utility function, we abandon it. Then, we put forward the interactive multi-object negotiation method because it can solve these negotiation problems without the negotiators' utility functions. The method utilises the different negotiators' cross concessions of the different objects and seeks for the conflict bottleneck of the conflicts and then solves the negotiation problems.